Transformation of an industrial facilities - revitalisation or adaptation = Przekształcenia obiektów przemysłowych - rewitalizacja czy adaptacja - Olejko, Wiesław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
At the turn of the century Polish cities witnessed radical changes due to the political, economic and social transformations which resulted in the technical, social, and cultural degradation of the existing former industrial buildings. On the wave of the common process of revitalization in recent years, many industrial buildings have been transformed.
Keywords: obiekty przemysłowe; przekształcenia obiektów przemysłowych; rewitalizacja; adaptacja; industrial facilities; transformation of industrial facilities; revitalisation; adaptation